2018
DOI: 10.16949/turkbilmat.417939
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Science Teachers’ views on STEM Approach

Abstract: Öz: FeTeMM yaklaşımı, 2017 yılından itibaren Fen Bilimleri Dersi Öğretim Programı'nda yer almaktadır. Bu nedenle öğretim programının uygulayıcıları olan öğretmenlerin FeTeMM konusundaki görüşlerinin belirlenmesi önemli hale gelmiştir. Bu çalışmanın amacı, Fen Bilimleri öğretmenlerinin FeTeMM yaklaşımı hakkındaki görüşlerini belirlemektir. Çalışma, 2017-2018 eğitim öğretim yılında Türkiye'nin bir doğu vilayetinde farklı ortaokullarda görev yapan 10 Fen Bilimleri öğretmeni ile yürütülmüştür. Nitel araştırma olar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 9 publications
(17 reference statements)
0
19
0
Order By: Relevance
“…Among the positive aspects of STEM, prospective teachers were interested in the development of creativity, reporting that "STEM made me think creatively" and "STEM has led us to discover that we can produce something new", reflecting the findings of Yildirim and Turk (2018) and Bakirci and Kutlu (2018) who similarly have reported that prospective STEM teachers improved creativity. Another research finding that teachers commonly believed that STEM is necessary in the development of creativity is Campbell et al (2012).…”
Section: Prospective Teachers' Opinions On Stem Activitiesmentioning
confidence: 84%
See 1 more Smart Citation
“…Among the positive aspects of STEM, prospective teachers were interested in the development of creativity, reporting that "STEM made me think creatively" and "STEM has led us to discover that we can produce something new", reflecting the findings of Yildirim and Turk (2018) and Bakirci and Kutlu (2018) who similarly have reported that prospective STEM teachers improved creativity. Another research finding that teachers commonly believed that STEM is necessary in the development of creativity is Campbell et al (2012).…”
Section: Prospective Teachers' Opinions On Stem Activitiesmentioning
confidence: 84%
“…The positive aspects of STEM activities included encouraging group work, assisting students to produce original work, enabling them to do research, and ensuring that the information learned is permanent. Similarly, there are researches reporting positive prospective and experience teachers' opinions on STEM in the literature (Bakirci & Kutlu, 2018;Campbell et al, 2012;Guder & Gurbuz, 2018;Aydin-Gunbatar et al2018;Kizilay, 2016;Ozbilen, 2018;Park et al, 2016;Thomas, 2014;Ugras, 2017;Wang, 2012;Yildirim & Turk, 2018).…”
Section: Prospective Teachers' Opinions On Stem Activitiesmentioning
confidence: 94%
“…In many studies (Altan et al, 2018;Jesionkowska et al, 2020;Windschitl, 2009), it has been emphasized that it is important to gain 21 st -century skills in this school process. After-school program activities related to STEM have helped students develop and use 21st-century skills such as complex communication and collaboration (Bakırcı & Kutlu, 2018;Changtong et al, 2020;Jerald, 2009;Levy & Murnane, 2004;Margot & Kettler, 2019;Siew et al, 2015). Another important concept is creativity.…”
Section: Discussionmentioning
confidence: 99%
“…Participants think that STEM implementations will contribute to students' achieving certain outcomes. In the study conducted by Bakırcı and Kutlu (2018), teachers stated that STEM activities provided learning by living, concretizing the subjects, meaningful learning and engineering topics to their students. In some studies (Bakırcı & Kutlu, 2018;Smyrnova-trybulska et al, 2016), it has been observed that students perceive the learning process in STEM activities more enjoyable, assume learning responsibilities, and have a positive attitude towards learning.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies carried out by universities on the effectiveness of STEM activities designed using teaching methods such as context-based learning (Yıldırım, 2018), mastery learning (Yıldırım & Selvi, 2017), and argumentation (Yıldırım & Turk, 2018). Additionally, opinions of teachers (Açıkgül Fırat, 2020;Akgündüz & Akpınar, 2018;Bakırcı & Kutlu, 2018;Eroğlu & Bektaş, 2016;Gülgün, Yılmaz, & Çağlar, 2017;Hebebci, 2019;Özbilen, 2018;Özcan & Koştur, 2018;Taştan-Akdağ & Güneş, 2017;Timur & İnançlı, 2018;Uğraş, 2017;Uğraş & Genç, 2018), students (Akgündüz & Akpınar, 2018;Aydın & Karslı Baydere, 2019;Dönmez, 2017;Gülhan & Şahin, 2016;Hebebci, 2019;Karakaya, Yantırı, Yılmaz, & Yılmaz, 2019;Taştan-Akdağ & Güneş, 2017;Yıldırım & Turk, 2018) and pre-service teachers (Bektaş & Aslan, 2019;Hacıoğlu, Yamak, & Kavak, 2016;Şahin, 2019;Timur & İnançlı, 2018;Uğraş & Genç, 2018;Yıldırım, 2020) on the STEM approach were examined. Studies on STEM education were compiled by Yıldırım (2020) using the ADDIE expansion, and the STEM teacher institutes education model was introduced.…”
Section: Introductionmentioning
confidence: 99%